Modeling, design and simulation of systems. 17th Asia Simulation Conference, AsiaSim 2017, Melaka, Malaysia, August 27-29, 2017, Proceedings /: 17th Asia Simulation Conference, AsiaSim 2017, Melaka, Malaysia, August 27-29, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available